Improving Coach Competence as an Effort to Improve Science and Technology-Based Sports Achievements at KONI Magetan Regency - Jatmiko, Tutur; Sidik, Rizky Muhammad; Utami, Tri Setyo; Aji, Wahyu Renandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Community empowerment is an essential initiative focused on promoting and fostering positive transformations in the areas of sports, social sciences, arts, and cultural community activities. In the realm of sports, community empowerment emphasizes enhancing the quality of human resources, physical fitness, and athletic success at provincial, national, and international stages, thereby shaping the community's identity as an important contributor to sports advancement. A primary objective of this community service initiative (PKM) is to create strategies for improving athletic performance by offering certified physical trainer training and guidance to the KONI Magetan Regency members, assisting them in succeeding at provincial, national, and international contests. Attaining success in sports demands a long-term, structured, and sustainable strategy, vital for developing regional and national sports identities. Community engagement is a crucial element in developing national sports strategies and programs. Empowering sports via the branch leaders of KONI Magetan Regency is essential for promoting community-oriented sports as well as competitive success. The techniques employed in this program consist of educating physical trainers and designing training programs. The education for physical trainers centers on crafting training regimens that cater to the unique requirements of various energy systems, the traits of specific sports disciplines, and the structuring of training over periods to improve athletes' biomotor abilities. Furthermore, the program includes the formulation of physical training strategies aimed at assisting athletes in achieving optimal performance according to set objectives. This training seeks to empower sports coaches at KONI Magetan Regency with the expertise to create impactful programs that enhance athletes' skills and contribute to success. The objective is to cultivate proficient coaches and elite athletes capable of representing Magetan Regency, East Java, and Indonesia on greater platforms.